Covid-19 : le retour à la plage dans quatre grandes villes méditerranéennes après le confinement du printemps 2020 : Marseille et Nice (France), Barcelone et Valence (Espagne) - Samuel Robert; Brieuc Cabioch; Marie-Laure-Tremelo; Nelly Pares; Éric Carroll; Alexandra Schleyer-Lindenmann (Développement Durable et Territoires)
The post-containment period of spring 2020 in Western Europe was a time of hope and hesitation about the possibility of a return to normality after the first act of Covid-19. This article reports on the specific case of the return to the beach in four major Mediterranean cities (two in Spain and two in France), where a user survey and field observations were conducted to identify the effects of the pandemic on practices and management. Between apprehension of the risk and desire for sociability, between the presence and relative absence of public authorities, the study reveals a clear distinction between the Spanish and French situations, directly related to the unequal violence of the shock caused by the first wave of the pandemic in these two countries.